2013
DOI: 10.1007/s10157-013-0814-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and glomerular podocytes in patients with chronic kidney diseases

Abstract: Urinary podocyte excretion reflects ongoing glomerular injury in various kidney diseases, and podocyte loss correlated with glomerulosclerosis and impaired selectivity of proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Podocalyxin[40] (PCX) is a highly negatively charged molecule which is abundantly expressed on the surface of podocytes and hence is a sensitive marker of these cells commonly used in podocyturia studies[13, 41, 42]; however, since some of the parietal cells covering Bowman's capsule also express podocalyxin[42], we used claudin-1 (CL-1) which, in glomeruli, is specifically expressed in parietal epithelial cells, as an exclusion marker. The cytospin slides were stained with antibodies against PCX (Invitrogen, Camarillo, CA.…”
Section: Methodsmentioning
confidence: 99%
“…Podocalyxin[40] (PCX) is a highly negatively charged molecule which is abundantly expressed on the surface of podocytes and hence is a sensitive marker of these cells commonly used in podocyturia studies[13, 41, 42]; however, since some of the parietal cells covering Bowman's capsule also express podocalyxin[42], we used claudin-1 (CL-1) which, in glomeruli, is specifically expressed in parietal epithelial cells, as an exclusion marker. The cytospin slides were stained with antibodies against PCX (Invitrogen, Camarillo, CA.…”
Section: Methodsmentioning
confidence: 99%
“…Urine sediment tests are inexpensive and safe, and positive findings with respect to casts and various cell types could be useful for the diagnosis of renal glomerular and tubular damage. Podocytes, which can be identified via podocalyxin expression in the urine, indicate the early stage of glomerular damage [8,9]. Round cells were negative for podocalyxin and the clinical stages of patients who are positive for round cells were different from those that have previously been associated with podocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Podocyte injury is considered to be one of the most critical factors in the development of proteinuria caused by glomerular filtration barrier dysfunction and continuous injury may cause severe apoptosis, leading to proteinuria, glomerulosclerosis and renal impairment; the major reason is that podocytes are highly differentiated cells with specific structural and biological functions, which are not renewable after sustained injury (1,2). To date, a large number of studies have indicated that podocyte injury, loss and dysfunction have an important role in pathologies including focal segmental glomerulosclerosis and membranous nephropathy (3)(4)(5). Immunosuppressants (e.g., steroids or cyclosporine A) have been used based on anecdotal evidence to treat NS (6).…”
Section: Introductionmentioning
confidence: 99%